The impact of credit default swap trading on loan syndication - Daniel Streitz (Sonderforschungsbereich/Transregio 15 - Governance and the Efficiency of Economic Systems (GESY), 2015)
We analyze the impact of CDS trading on bank syndication activity. Theoretically, the effect of CDS trading is ambiguous: on the one hand, CDS can improve risk-sharing and hence be a more flexible risk management tool than loan syndication; on the other hand, CDS trading can reduce bank monitoring incentives. We document that banks are less likely to syndicate loans and retain a larger loan fraction once CDS are actively traded on the borrower's debt. We then discern the risk management and the moral hazard channel. We find no evidence that the reduced likelihood to syndicate loans is a result of increased moral hazard problems.
Keywords: G21; G32; 330; Loan Sales; Credit Default Swaps; Syndicate Structure; Syndicated Loans